Aortitis: an interdisciplinary challenge - Shchetynska-Marinova, Tetyana; Sadick, Maliha; Keese, Michael; Sigl, Martin (In vivo, 2021)
The term ‘aortitis’ comprises a heterogeneous spectrum of diseases, with varied etiology and clinical presentations, whose common characteristic is the inflammation of the aortic wall. Since aortitis can mimic almost all common cardiovascular disorders, its clinical recognition remains a challenge. Some cases of aortitis remain undetected for a long time and may be diagnosed after severe life-threatening complications have already arisen. The diagnosis of aortitis is based on the presence of homogeneous circumferential thickening of the aortic wall detected on aortic imaging, or typical histological features in combination with clinical findings and laboratory parameters. Management of aortitis is usually conservative (immunosuppressive drugs in noninfectious aortitis; antimicrobial drugs in infectious). However, if vascular complications such as aortic aneurysm, rupture, or steno-occlusive events appear, aortic surgery or endovascular therapy may be required. This review article summarizes the current knowledge regarding the etiology, clinical presentation, diagnosis, and treatment of inflammatory diseases of the aorta to promote better clinical management of these entities.
Gesehen am 29.03.2021